Rapid thermal annealing of thin doped and undoped spin-on glass films - Ventura, L.; Slaoui, A.; Muller, J.c.; Siffert, P. (Materials science & engineering. B, Solid-state materials for advanced technology, 1995)
Rapid thermal annealing (RTA) was investigated for curing doped and undoped spin-on glass films deposited onto silicon substrates. The annealed undoped spin-on glass (SOG) films present an important densification of the layers as a function of temperature and a reduction in the interfacial state density. The possibility of using rapid thermally annealed spin-on doped glass (SOD) films as a doping source as well as a surface passivation layer was investigated. The results show that the combination of spin-on film (after dilution of the solution with methanol) deposition and RTA can produce shallow lightly doped emitters. Sheet resistances lower than 150 Ω/□ are easily reached. Moreover, the minority-carrier diffusion length is improved owing to the gettering effect induced by phosphorus diffusion. The use as a passivation layer of the SOG or the remaining SOD oxide film makes this technique favourable for applications such as the fabrication of solar cells.